Evaluation of different blended fertilizer types and rates for better production of Bread Wheat (Triticum aestivum L.) at Adiyo District, South West Ethiopia - Guja, Ute; Abreham, Konjit; Mekuria, Tatek; Tsegaye, Henok (Journal of Science and Development, 2020)
ABSTRACT Bread wheat (Triticum aestivum L.) is an important food crop and source of income for farmers. It is the most responsive crop to fertilizer application. Field experiment was carried out on farmer's field in 2016/17 and 2017/18 main cropping seasons to evaluate the response of bread wheat to different blended fertilizers types and rates at Adiyo district, Southwestern Ethiopia. Eight treatments: Control (T1), four rates of NPSB: (46N,54P2O5,10S, 1.07B (T2); 69N, 72P2O5, 13S, 1.4B (T3), 92N, 90P2O5, 17S, 1.7B (T4) and 92N, 36P2O5, 7S, 0.71B (T5)) and three rates of NPSBCu: T2+Cu (T6), T3+Cu (T7), T4+Cu (T8) were laid out in randomized complete block design with three replications. Crop parameters measured were analyzed using proc GLM procedures in the SAS 9.3 version. Analysis was also performed to investigate the economic feasibility of the fertilizers for wheat production. Results indicated that application of both type and three rates of each fertilizer significantly (p < 0.05) affected all tested parameters except thousand seed weight, which was improved by only T4. The highest biomass (14.80 ton ha-1) and grain yield (6.537 ton ha-1) were obtained from application of highest rate of NPSB+Cu (T8) whereas the lowest biomass (9.36 ton ha-1) and grain yield (3.657 ton ha-1) were obtained from untreated soil. The application of NPSB+Cu (T8) also gave highest net benefit of Birr 46637.10 and acceptable MRR% was 151.02%. Hence farmers at study area and similar agro-ecology could use NPSB+Cu @ a rate (92N, 90P2O5, 17S, 1.7B) and 600 gm Cu as foliar application. However, further verification study is needed to give reliable and consistent recommendation.